Peranan Strategi Manajemen Pemasaran Dalam Meningkatkan Volume Penjualan Produk Brand Garuda Di PT. Sinar Niaga Sejahtera Wilayah Bali Nusra - Agung Wijoyo; Sintya Murni; Syafira Zahra; Zubair Nabiil Musyaffa Yusuf (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Sinar Niaga Sejahtera is a company engaged in the distribution of food and beverages specifically from Garudafood products. Founded by Mr. Sudhamek as the owner of SNS in 1994, SNS's role is very decisive for the development of Garudafood. Because of its role, various kinds of Garudafood products can be obtained by consumers in remote areas throughout Indonesia. SNS already has a number of depots serving hundreds of thousands of customer outlets throughout Indonesia. The aim of this research is to determine the marketing strategy implemented based on the internal and external environment in increasing the sales volume of Garuda Brand products at PT. Sinar Niaga Sejahtera. The types of data used are quantitative data and qualitative data. Quantitative data is calculated data or data in the form of numbers based on the results of questionnaires from respondents which include opportunities, threats, strengths and weaknesses of Garuda Brand products at PT Sinar Niaga Sejahtera. Based on the results of the analysis, it can be concluded that judging from the internal and external factor indicators, the position of the company PT. Sinar Niaga Sejahtera is based on Growth Strategy, namely a strategy aimed at stabilizing the company or a strategy implemented without changing the direction of the marketing strategy. The strategies that can be used are: Market diversification strategy, namely a strategy that uses its strengths to take advantage of long-term opportunities. The suggestions given are that the company should also try to improve its strengths to reduce the weaknesses it has so far so that the company's position can be raised and able to compete competitively. And by anticipating weaknesses so that they do not become threats, companies should be careful with the current situation, by understanding the market more seriously to try to rise through exploiting existing opportunities and minimizing the threats they face through new breakthroughs to find and enter market opportunities. existing ones, for example by marketing new products that are more acceptable to consumers in accordance with current consumer buying interests.